2001
DOI: 10.1177/104063870101300404
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Maedi-Visna (Ovine Progressive Pneumonia) Virus Seroconversion in Field Sheep Samples

Abstract: The aim of this work was to investigate whether an enzyme-linked immunosorbent assay (ELISA) was useful for early detection of maedi-visna virus (MVV) infection in sheep under field conditions. An ELISA based on p25 recombinant protein and a gp46 synthetic peptide was used. Sequentially obtained serum samples (n = 1,941) were studied for 4 years. ELISA results were compared with those of the agar gel immunodiffusion (AGID) test, and results of both tests were compared with a reference result established using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 30 publications
(52 reference statements)
2
21
0
9
Order By: Relevance
“…The association found in this study between clinical mastitis, seropositivity to MVV by ELISA and viral detection in the mammary gland was high, with one exception. Among the serologic tests used in this study to detect MVV antibodies, the increased sensitivity observed in the ELISA with respect to AGID was expected according to previous studies [38,44] and confirmed by the presence of viral genome and proteins in histopathological observations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The association found in this study between clinical mastitis, seropositivity to MVV by ELISA and viral detection in the mammary gland was high, with one exception. Among the serologic tests used in this study to detect MVV antibodies, the increased sensitivity observed in the ELISA with respect to AGID was expected according to previous studies [38,44] and confirmed by the presence of viral genome and proteins in histopathological observations.…”
Section: Discussionsupporting
confidence: 81%
“…A seronegative accredited Latxa breed flock was used for supply of control animals. The serological test for classification of flocks and animals was based on a recombinant ELISA test (Elitest ® , Hyphen BioMed, Neuville/Oise, France, formally known as Innotest ® , Innogenetics, Ghent, Belgium) [38,44]. A standard agar gel immunodiffusion test (AGID) for MVV (CVL, Weybridge, United Kingdom) was also applied [46].…”
Section: Animals Infection and Mammary Gland Statusmentioning
confidence: 99%
“…Possui fácil aplicabilidade e alta especificidade (Varea et al, 2001). Como desvantagem, o teste somente detecta altos níveis de imunoglobulinas, o que permite a ocorrência de falso-negativos no rebanho (McConnell et al, 1998).…”
Section: Introductionunclassified
“…However, the diagnostic techniques should be chosen according to the cost-benefit ratio, commercial availability, and access to diagnostic laboratories (GOUVEIA, 2012). When only AGID diagnosis is available, given its high specificity (Table 1), monitoring by AGID in the early stages of SRLV control programs can be used alone (VAREA et al, 2001;PINHEIRO et al, 2006a;GOUVEIA, 2012). This strategy allows falsenegative goats to remain in the herd for a longer time, thus contributing to virus transmission.…”
Section: Prophylaxis and Strategies For The Control And Eradication Omentioning
confidence: 99%
“…Other serological techniques such as WB and dot blot (DB) have more limited use due to cost, speed, convenience, or availability. The World Organization for Animal Health (OIE) recommends the use of AGID or ELISA for diagnosis of SRLV infection (VAREA et al, 2001;OIE, 2008;REINA et al, 2009). …”
Section: Diagnostic Testsmentioning
confidence: 99%